The effect of vitamin D provision on biomarkers of inflammation in bronchial asthma in children - N. A. Belykh; I. V. Pisnyur; A. A. Nikiforov; L. V. Nikiforova (Аллергология и Иммунология в Педиатрии)
Introduction. Asthma is a widespread disease in childhood and has a persistent tendency to increase. Therefore, the search for factors influencing this process, as well as biomarkers reflecting the degree of asthma control, is an urgent problem.   Objective. To study the relationship of vitamin D levels with the serum periostin and TGF-β1 concentration in children with asthma.   Materials and methods. The cross-sectional (one-stage) study included 80 children aged 6 to 17 years (average age — 12 ± 3.2 g). The subjects were divided into 2 groups: children with asthma — group 1 (n = 40); group 2 — the control group (n = 40). In all children, the assessment of the concentration of 25(OH)D, periostin and TGF-β1 in the blood serum was studied.   Results. Median (Me) 25(OH) in patients with asthma was statistically significantly lower than in children of the comparison group (16.7 ng/ml, versus 25.7 ng/ml, p = 0.017), and did not depend on the severity of the disease, corresponded to a deficiency condition in both mild (16.2 ng/ml) and with an average severity of asthma (16.8 ng/ml) (p = 0.041). Me of periostin in 1st group was within the normal range (730.2 ng/ml), but statistically significantly exceeded the indicator of 2nd group (539.7 ng/ml, p < 0.05) and did not depend on the age and duration of asthma. High rates of periostin were observed in children with moderate severity of asthma with a disease experience of 4–6 years (617.2 ng/ml). Me of TGF-β1 in both groups corresponded to normal values (309.0 and 369.6 pg/ml, respectively, p > 0.05) and did not depend on the age and duration of asthma.   Conclusions. VD deficiency is registered in children with asthma 2 times more often than in healthy children in Ryazan region. The serum concentration of periostin increased in proportion to the severity of asthma. Vitamin D deficiency can be one of the risk factors for the development of asthma and lead to an imbalance in the periostin and TGF-β system.